2019
DOI: 10.1007/s12035-019-01842-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Glia-Derived Neuroinflammation: a Novel Hallmark in Lafora Progressive Myoclonus Epilepsy That Progresses with Age

Abstract: Lafora disease (LD) is a rare, fatal form of progressive myoclonus epilepsy. The molecular basis of this devastating disease is still poorly understood and no treatment is available yet, which leads to the death of the patients around 10 years from the onset of the first symptoms. The hallmark of LD is the accumulation of insoluble glycogen-like inclusions in the brain and peripheral tissues, as a consequence of altered glycogen homeostasis. In addition, other determinants in the pathophysiology of LD have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 45 publications
11
72
0
Order By: Relevance
“…Although the primary cause of PMEs is different in each case, recent reports suggest that oxidative stress and neuroinflammation are common traits in all these conditions [161][162][163]. This reinforces the idea that oxidative stress and neuroinflammation are at the crossroad of rare neurodegenerative disorders.…”
Section: Progressive Myoclonus Epilepsies (Pmes)supporting
confidence: 57%
See 1 more Smart Citation
“…Although the primary cause of PMEs is different in each case, recent reports suggest that oxidative stress and neuroinflammation are common traits in all these conditions [161][162][163]. This reinforces the idea that oxidative stress and neuroinflammation are at the crossroad of rare neurodegenerative disorders.…”
Section: Progressive Myoclonus Epilepsies (Pmes)supporting
confidence: 57%
“…Recently, we have analyzed by RNA-Seq technology the genes that were differentially expressed in the brain of Epm2a −/− and Epm2b −/− mice in comparison to control animals and observed that Epm2a −/− and Epm2 −/− mouse brains overexpress a common set of genes mostly related to inflammation [162]. We also defined that reactive glia was responsible for the expression of these genes.…”
Section: Lafora Disease (Ld)mentioning
confidence: 99%
“…These results clearly indicated that neuroinflammation is an important trait to be considered in order to fully understand the pathophysiology of LD (Ref. 37).…”
Section: Lafora Disease (Ld Epm2 Omim #254780)mentioning
confidence: 74%
“…Epilepsy is a common symptom in patients with brain tumors, head injuries, and genetic diseases [ 89 , 94 , 139 , 140 ]. Epileptic patients have been reported to have high levels of IL-1ß, IL-1 receptors (IL-1Rs), IL-8, IL-12, MIP-1b, translocator protein (TSPO), toll-like receptor-4 (TLR4), high mobility group box 1 (HMGB1), TNF-α, and cytokine-related genes [ 15 , 47 , 89 , 139 , 140 ]. IL-1ß and TNF-α are the most widely studied, and the concentration of these cytokines is known to be important for protogenic status and inhibition of seizures [ 48 ].…”
Section: Epilepsymentioning
confidence: 99%
“…In this Lafora disease (LD) rodent model, upregulated inflammatory-related genes have been reported through RNA-sequencing ( Table 3 ). Approximately 60% of the upregulated proteins were found to be related to microglia [ 89 ]. LD is a genetically induced epilepsy.…”
Section: Epilepsymentioning
confidence: 99%